Persepsi Pengunjung Terhadap Pendapatan Rumah Makan di Tanak Maik Masbagik Pasca Pandemi Covid 19 - Rachman, Dedy febry; Amri, Syaiful (Jurnal Ilmu Sosial dan Humaniora, 2023)
The purpose of this study was to determine visitor perceptions of income for the Tanak Maik restaurant (lesehan) income, in Masbagik Utara Baru Village, Masbagik District. The type of approach used is a quantitative descriptive approach, by systematically describing the facts and characteristics of the objects and subjects studied appropriately. In the study, the population was all visitors to the Tanak Maik (Lesehan) restaurant. In taking the sample, the researcher uses the Quota sampling technique. The researcher determines the size of the number of respondents to become members of the sample. Based on analysis considerations, the researcher determined to set a quota of 40 respondents which were divided into 4 sittings, namely full moon sittings, chords sitting, istiqomah sitting, and wine sitting. So that each lesehan get 10 respondents. And data collection techniques used are observation, interviews, documentation. The type of interview used by the researcher was a direct interview with the instrument used in the form of a questionnaire (Quisioner). Based on the research data, it can be concluded that based on the results of the respondent's data, the level of satisfaction was 49.45 or classified as a satisfied category.